ANALISIS PENGARUH DUKUNGAN SELEBRITI, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERFCAYAAN KONSUMEN (STUDI PADA KONSUMEN KLINIK LARISSA AESTHETIC CENTER SEMARANG) - Fauziah, Syifa; Sutono, Sutono; Wismar'ein, Dian (Universitas Muria Kudus, 2025)
The purpose of this study was to determine whether celebrity endorsements, brand image and product quality affect consumer trust and consumer trust affect purchasing decisions. The object of this research is the consumers of the Larissa Aesthetic Center Semarang. This research was conducted by distributing questionnaires to 150 respondents with a purposive sampling technique, in which the researcher determined certain criteria to select consumers who would be used as respondents. These criteria make not all consumers of the Semarang Larissa Aesthetic Center able to be respondents in this study. The data analysis method uses Structural Equation Modeling (SEM) with a confirmation approach and uses the AMOS program. The results of the analysis in te study are as follows: (1) celebrity support had a negative and significant effect on consumer trust. (2) brand image has a positive but not significant effect on consumer trust (3) product quality has a negative but not significant effect on consumer confidence (4) celebrity endorsement has a positive and significant effect on purchasing decisions (5) brand image has a positive and significant effect on purchasing decisions (6) product quality has a positive and significant effect on purchasing decisions (7) consumer trust has a negative but not significant effect on purchasing decisions.